Alterations in the phenotype of CMV-specific and total CD8+ T-cell populations in Wegener's granulomatosis. - Lamprecht, P; Vargas Cuero, A; Muller, A; Csernok, E; Voswinkel, J; Maass, M; Solbach, W; Gross, W; Klenerman, P (2003)
Wegener's granulomatosis (WG) is an autoimmune disease of as yet unknown etiology. To date it has remained obscure what causes WG or determines disease progression. Case reports suggest that viral infections such as cytomegalovirus (CMV) reactivation may contribute to disease flares. In this study we found a skewing of the phenotype of CMV-specific CD8+tet(ramer)+ T-cells in WG. A marked proportion of these cells displayed a late differentiated "effector memory" T-cell phenotype with decreased expression of CD28 and CD62L, and heterogeneous CD27 expression, features which were also seen in CD8+tet- T-cells in WG, but not in controls. Our results might reflect profound generalized changes in the CD8+ T-cell compartment also affecting virus-specific T-cell responses in WG.